Application of a new real-time polymerase chain reaction assay for surveillance studies of lymphocystis disease virus in farmed gilthead seabream - Valverde, Estefania J. (BMC Vet Res, 2016)
BACKGROUND: Lymphocystis disease (LCD) is the main viral infection reported to affect cultured gilthead seabream (Sparus aurata) in Europe. The existence of subclinical Lymphocystis disease virus (LCDV) infection in this fish species has been recognised by using polymerase chain reaction (PCR)-based methods. Nevertheless, these methods do not provide quantitative results that can be useful in epidemiological and pathological studies. Moreover, carrier fish have been involved in viral transmission, therefore the use of specific and sensitive diagnostic methods to detect LCDV will be relevant for LCD prevention. RESULTS: We have developed a real-time PCR (qPCR) assay to detect and quantify LCDV. The assay was evaluated for viral diagnosis in surveillance studies in gilthead seabream farms, and also to identify viral reservoirs in a hatchery. The prevalence of LCDV infection in the asymptomatic gilthead seabream populations tested varied from 30 to 100 %, including data from one farm without previous records of LCD. Estimated viral load in caudal fin of subclinically infected fish was two to five orders of magnitude lower than in diseased fish. The qPCR assay allowed the detection of carrier fish in broodstock from a farm with a history of clinical LCD in juvenile fish. In addition, the quantitative detection of LCDV was achieved in all samples collected in the hatchery, including fertilized eggs, larvae and fingerlings, and also rotifer cultures and artemia metanauplii and cysts used for larval rearing. CONCLUSIONS: The qPCR assay developed in this study has proved to be a rapid, sensitive, and reliable method for LCDV diagnosis, which could be valuable to identify LCDV reservoirs or to study viral replication in gilthead seabream.